Restorative Justice as a New Paradigm in the Enforcement of Hate Speech Laws in Indonesia - Asep Nana Mulyana; Sukron Ma’mun; Zul Karnen (Sekolah Tinggi Ilmu Hukum Adhyaksa, 2025)
Law enforcement against hate speech in Indonesia has predominantly relied on a repressive approach under the Electronic Information and Transactions Law (ITE Law), often failing to uphold the principles of substantive justice. This article evaluates the effectiveness of the current approach and proposes restorative justice as a more humane and participatory alternative paradigm. Using the socio-legal research method, this study analyzes the concept of restorative justice in addressing hate speech through interviews with legal stakeholders and legal literature and scientific analyzes. This discussion finds, first, that law enforcement against hate speech under the ITE Law remains suboptimal and fails to fully reflect the principles of substantive justice. A punitive-centric approach often neglects critical social dimensions, including the perpetrator’s background, the victim’s circumstances, and the broader cultural context—resulting in legal disparities and the risk of societal over-criminalization. Second, a shift toward restorative justice is imperative. This paradigm offers a more humanistic and transformative framework by prioritizing the restoration of social relations, victim recovery, and the active accountability of offenders. Its inclusive and dialogical nature fosters reconciliation and contributes to a more just, inclusive, and sustainable legal system.